Docência universitária inovadora: um estudo nos cursos de Educação Física em IFES da região do Triângulo Mineiro - Silva, Wellington dos Reis (2021)
This study is part of Research Line “Educational Knowledge and Practices” and aims to understand College teaching in an innovative perspective, in Physical Education Courses in Federal Institutions of Higher Education in the Region of Triângulo Mineiro, Minas Gerais, Brazil. The questions that guided the investigation were the following: What evidences of innovative teaching can be learned in Physical Education courses in the Triângulo Mineiro IFES? How does teaching learning occur in this perspective? What are the main concepts that guide the pedagogical practice of teachers appointed as innovators? What importance do these teachers attach to didactic-pedagogical knowledge at the University? For them, what does it mean to be an innovative teacher? How do these teachers develop professionally? This is an exploratory type research, with a qualitative approach and that makes approximations to the Dialectical Historical Materialism method. The empirical material was obtained through a questionnaire answered by the course coordinators and by students who indicated the teachers who develop teaching practices considered innovative. In addition, the teachers' Curriculum Lattes, documents, laws and guidelines that portray the history of the institutions, Higher Education and Physical Education Courses in Brazil were analyzed. For the triangulation of information, we carried out reflective interviews to teachers who are considered as being innovators, by their students. We used Bardin’s content analysis technique (1977). The results indicated that the meaning of “innovative teaching” for the searched professors is related to the break with the conservative Education paradigm by which the teacher is the center of the teaching and learning process and their students are considered as mere spectators of linearized and unquestionable knowledge. Therefore, for teachers, improving the quality of their professional activities, both in teaching, research and extension is based on dynamism, overcoming, collaborating and organizing academic work in College education. These bases, when articulating teaching with research, are based on the principles of critical thinking, methodical doubt and on the development of students' intellectual autonomy. The defended thesis is expressed in the following proposition: innovative teaching is constituted from the triad teacher-student-knowledge in a dialectical perspective, anchored by dialogism, collaboration and engagement in the teaching-learning process with research. The research indicates the need for universities to be able to undertake an institutional project for permanent training and professional development for teachers, with a view to improving undergraduate education.